The Influence of Leadership on Employee Turnover Intention at The Westin Resort & Spa Ubud, Bali - Anak Agung Istri Julistya Dewi; Irene Hanna H. Sihombing; Ni Made Suastini (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the extent to which leadership (X) influences employee turnover intention (Y) at The Westin Resort & Spa Ubud, Bali. This study uses a quantitative approach with a population of 112 employees of The Westin Resort & Spa Ubud, Bali, using a saturated census sampling method. Data were collected through a questionnaire with a 5-point Likert scale to measure 14 statements from the leadership and turnover intention variables. The data obtained were then analyzed using simple linear regression with the help of the SPSS 23 version 23 application for windows. By using simple linear regression, it can be obtained that leadership has a significant negative effect on employee turnover intention with a value of -tcount < -ttable, namely -10.898 < -1.659. Leadership has a negative value with a beta value of -0.459 on turnover intention.